Smart active transport infrastructure (SmATI) to achieve sustainable mobility - Nili, Negar (Curtin University, 2022)
This study develops a framework for applying technology to increase active transport. The findings suggest that in order to successfully apply technology to increase active transportation, first, users of these technologies need to be identified. Then, the type of technology should be specified. Finally, safety and security, simplicity, connection and integration, awareness; and prioritisation needs to be considered when technology is applied.